Eskatologi Bencana dan Keteguhan Hati: Analisis Nilai Humanisasi, Liberasi, dan Transendensi dalam Novel Hafalan Shalat Delisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to reveal the manifestation of prophetic values in the novel Hafalan Shalat Delisa by Tere Liye, which is set against the backdrop of the 2004 Aceh Tsunami tragedy. Using Kuntowijoyo's Prophetic Literature approach, this research dissects how literary texts respond to disaster situations not only as physical tragedies but as transcendental moments. The research method used is descriptive qualitative with hermeneutic analysis techniques. The results showed that this novel contains three pillars of prophetic ethics: (1) Humanization is reflected in social solidarity and the affection of the father figure amidst destruction; (2) Liberation is manifested in the main character's struggle to free herself from the shackles of psychological trauma and physical limitations post-amputation; and (3) Transcendence is present as the core narrative through the transformation of the main character's worship motivation—from material orientation towards total sincerity to God. This novel confirms that prophetic literature can serve as a medium for inner healing as well as effective character education.